Pride-Based Self-Affirmations and Parenting Programs - Hill, Zoelene; Spiegel, Michelle; Gennetian, Lisa A. (Frontiers in Psychology, 2020)
We newly apply the concept of self-affirmation typically used in the domain of health and education to the domain of parenting. Recruiting parents of children age 13 or younger (n = 1,044), we test how eliciting positive self-concept affects interest in receiving parenting materials and participating in a parenting program. We find that an adapted, pride-based written self-affirmation exercise increased parents’ positive self-concept and their interest in parenting programs and resources, particularly among parents with a high baseline fear of judgment associated with seeking help. Implications for applying insights from psychology as a strategy to mitigate fear of judgment to optimize participation in an evidence-based parenting program at scale, are discussed.